2017
DOI: 10.1002/ep.12751
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive removal of arsenic from aqueous solutions using magnetite nanoparticles and silica‐coated magnetite nanoparticles

Abstract: Magnetite nanosorbents are known with high sorption capacity and ease of solid phase separation from surrounding liquid by the imposed external magnetic field. In this study, magnetite nanoparticles (MNPs) and silica‐coated magnetite nanoparticles (Si‐MNPs) were prepared and used for the removal of arsenic (III) from aqueous solutions. The nanosorbents were characterized by transmission electron microscope, X‐ray diffraction, Fourier transform infrared spectroscopy, and vibrating sample magnetometer. The spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Electrochemical treatments, flocculation and membrane filtration is a high cost techniques, process complexity, membrane fouling and low permeate flux. On the contrary, adsorption is an ideal technique to remove toxic pollutants from water for its simplicity, high efficiency, ease of operation, regeneration characteristics [3], and can remove heavy metals found in water at low concentrations [16]. Fortunately, the evolution of nanotechnology has highlighted this issue [2].…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical treatments, flocculation and membrane filtration is a high cost techniques, process complexity, membrane fouling and low permeate flux. On the contrary, adsorption is an ideal technique to remove toxic pollutants from water for its simplicity, high efficiency, ease of operation, regeneration characteristics [3], and can remove heavy metals found in water at low concentrations [16]. Fortunately, the evolution of nanotechnology has highlighted this issue [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, the removal of nano-adsorbent from water solutions is difficult for the small size of these particles. So, magnetic nanoparticles overcome this defect by removing these nanoparticles (NPs) and hazardous elements magnetic properties change and biodegrade in biological systems, it was also found that the bare magnetic nano-adsorbent were exposed to oxidation and loss of its magnetic properties at pH lower than 4 [3]. So, coating of magnetic NPs with silica is a commonly used procedure to obtain magnetic sorbents; this is due to silica stability and versatility of its surface modification [6].…”
Section: Introductionmentioning
confidence: 99%
“…So, coating of magnetic NPs with silica is a commonly used procedure to obtain magnetic sorbents; this is due to silica stability and versatility of its surface modification [6]. Silica coated magnetic nanoparticles with a magnetic core and a silica shell has the advantages of both materials with no apparent effect on magnetic properties that characterize the nano-magnetite [3]. Using of this magnetic nano-adsorbent for removal of pollutants from water continues to progress nowadays.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] This nanoparticle has been prepared by different methods such as precipitation, 41 electrooxidation, 42 and coprecipitation. 43 Because of being oxidized in an acidic medium 44 and formation of large aggregation, pure magnetic nanoparticles (Fe 3 O 4 -NP) are coated with different materials such as silica 45 and surfactants 46 to form a stabilized core-shell for further functionalization with various nanoparticles and ligands according to their application. 47 For the first time, in this work, the novel Fe 3 O 4 @NCs/ TiCl nanocomposite is introduced into gel-state polyvinyl acetate (PVAc)-based electrolyte as a nanofiller to decrease the crystallinity of the polymer, enhance the diffusion of redox couple ions, and prepare a nanocomposite gel electrolyte for quasisolid-state dye-sensitized solar cells (QS-DSSCs).…”
Section: Introductionmentioning
confidence: 99%